In Silico Analysis of Chalcone Derivatives as Potential Antibacterial Agents against DHPS Enzyme - Ilma Amalina; Ni Nyoman Tri Puspaningsing; Hery Suwito (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2023)
Chalcone and its derivatives have been reported to perform as antibacterial agents. With the increasing threat of antibacterial resistance in pharmaceutical sector today, the discovery of new antibacterial agents is essential to accomplish good health and well-being in supporting Sustainable Development Goals (SDGs) point 4. In silico analysis is a method used to evaluate some candidates of active compounds before the synthesis process is conducted. This study aims to investigate three chalcone derivatives as potential antibacterial agents using in silico method of molecular docking. The three chalcone derivatives, 3-(4-methoxyphenyl)1-phenylprop-2-en-1-one (1), 1-(4-aminophenyl)-3-(4- methoxyphenyl) prop-2-en-1-one (2) and 1-(4-bromophenyl)-3-(4-methoxyphenyl)prop-2-en-1-one (3), were designed as pABA competitive inhibitor on DHPS and analyzed against Eschericia coli. This inhibitory mechanism was folate synthesis inhibition as precursor to DNA and RNA synthesis. Molecular docking of three chalcone derivatives with DHPS was generated using Autodock4. The results of this study showed that free energy binding (kcal/mol) of compounds (1), (2) and (3) were -6.27, -5.35 and -5.77, respectively. Besides, the Ki constant for three compounds in order were 25.50 µM, 120.32 µM and 58.84 µM, respectively. In fact, the molecular docking positions illustrated that three chalcone derivatives occupied the active site cleft. Specifically, compound (1) indicated the best outcome among the two other candidates. Meanwhile, sulfadiazine molecular docking as positive control showed lower free binding energy (-0.86 kcal/mol) and Ki constant (233.19 mM) compared to three other candidates. Therefore, three chalcone derivatives analyzed in this study demonstrated a role as potential antibacterial agents.